ECONOMIC VALUATION OF GRONJONG WARITI ECOTOURISM AREA IN KEDIRI REGENCY - Rachintha Fica Novita Sari; Totok Hendarto; Rosidah Wahyu Ningtyas (Universitas Mataram, 2026)
Ecotourism development in Indonesia requires optimal management of available resource potential. Gronjong Wariti Ecotourism, located in Mejono Village, Plemahan District, Kediri Regency, is a community-based tourism destination that optimizes the balance between terrestrial ecosystems and river aquatic environments into fishery ecotourism. This tourism site adopts an educational tourism concept with facilities including tilapia, catfish, and comet fish ponds for live feeding activities, as well as fish therapy using Garra rufa. This research aims to analyze visitor assessments and calculate the economic value of Gronjong Wariti Ecotourism area using the Travel Cost Method approach. The study employs a descriptive method with quantitative and qualitative approaches through data collection techniques including observation, interviews, questionnaires, and documentation. The research sample of 30 respondents was determined using the linear time function formula. Research variables include independent variables namely travel costs, distance, income, education, age, gender, and transportation, as well as the dependent variable of visit demand quantity. The Travel Cost Method is used to calculate the economic value of resources with a regression model to determine the influence of each factor and calculate consumer surplus through Willingness to Pay analysis. The research results are expected to provide recommendations for managers regarding ecotourism area development and contribute academic information about economic valuation of fishery tourism areas.